Governing Waqf Ahli In Indonesia: A Socio-Legal Analysis of Juridical Challenges And Hybrid Governance Model - Hanan Salem Masoud Belgasem; Dzulkifli Noor; Ali Wafa; M. Abdul Gofur; Ab. Jalhani (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
This study examines the governance of waqf ahli (family waqf) in Indonesia through a socio-legal perspective, focusing on its juridical challenges at the intersection of inheritance and Islamic philanthropy. Existing studies largely emphasize normative fiqh dimensions, with limited attention to how waqf ahli operates in practice within plural legal systems. This study fills a gap in the literature by analyzing the socio-legal dynamics of family waqf governance and its implications for legal certainty and institutional effectiveness. Using a qualitative socio-legal approach, the research combines normative legal analysis with empirical data from West Java, Jakarta, and Madura. The findings show that Muslim families construct wealth through a dual logic: inheritance continuity and perpetual charity. However, this integration generates governance challenges, including weak institutional structures, overlapping roles between heirs and managers, and ambiguity in ownership and decision-making. These issues are exacerbated by inadequate legal frameworks that do not fully accommodate the specific characteristics of waqf ahli, leading to frequent intra-family disputes and inefficient asset management. To address these challenges, this study proposes a Hybrid Waqf Governance model that integrates familial participation with formal institutional management, emphasizing legal clarity, role standardization, and structured dispute resolution. This study contributes to socio-legal theory by demonstrating how legal pluralism shapes the governance of Islamic philanthropic institutions and by offering a context-specific governance model for improving accountability and sustainability of family waqf.